1998
DOI: 10.1016/s1097-2765(00)80019-2
|View full text |Cite
|
Sign up to set email alerts
|

PAK Kinases Are Directly Coupled to the PIX Family of Nucleotide Exchange Factors

Abstract: The PAK family of kinases are regulated through interaction with the small GTPases Cdc42 and Rac1, but little is known of the signaling components immediately upstream or downstream of these proteins. We have purified and cloned a new class of Rho-p21 guanine nucleotide exchange factor binding tightly through its N-terminal SH3 domain to a conserved proline-rich PAK sequence with a Kd of 24 nM. This PAK-interacting exchange factor (PIX), which is widely expressed and enriched in Cdc42- and Rac1-driven focal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
786
2
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(831 citation statements)
references
References 38 publications
37
786
2
6
Order By: Relevance
“…We recently found that Gβγ could directly interact with PAK1 and activate PAK1 in the presence of Cdc42 and a small GTPase exchange factor PIXα. PIXα is constitutively associated with PAK1 and can activate both Cdc42 and Rac in in vitro and overexpression assays [37,38]. In addition, we observed that Gβγ activated Cdc42 in the presence of PIXα and PAK1.…”
Section: Mechanism Of Cell Polarization In Regulation Of Chemotaxismentioning
confidence: 60%
See 1 more Smart Citation
“…We recently found that Gβγ could directly interact with PAK1 and activate PAK1 in the presence of Cdc42 and a small GTPase exchange factor PIXα. PIXα is constitutively associated with PAK1 and can activate both Cdc42 and Rac in in vitro and overexpression assays [37,38]. In addition, we observed that Gβγ activated Cdc42 in the presence of PIXα and PAK1.…”
Section: Mechanism Of Cell Polarization In Regulation Of Chemotaxismentioning
confidence: 60%
“…It is difficult to unambiguously determine the specificity of GEFs relying solely upon in vitro and overexpression assays because these GEF molecules, particularly their catalytic domains, share close amino acid sequence homology. Our study of PIXα provides an excellent example; PIXα was shown to activate both Rac and Cdc42 in vitro [37], but it only activates Cdc42 in neutrophils [10]. Thus, to unambiguously determine if P-Rex1 is the major Rac regulator in vivo, study of P-Rex1-null mice will be required.…”
Section: Mechanism Of Cell Polarization In Regulation Of Chemotaxismentioning
confidence: 99%
“…Enfin, l'inhibition de l'expression de βPIX par interférence ARN induit un phénotype tout à fait similaire à celui causé par la suppression de Scrib. βPIX a été identifiée comme partenaire de PAK (p21-activated kinase), une kinase effectrice des petites protéines G Cdc42 et Rac [27]. Ces petites protéines G existent sous une forme active liée au GTP et une forme inactive liée au GDP.…”
Section: L'interaction Cruciale De Scrib Avec Le Facteur D'échange Bpixunclassified
“…L'association de PIX avec un compartiment membranaire et secondairement son activité d'échange pour Rac/Cdc42 semblent être également régulées par phosphorylation sur les résidus sérine 525 et thréonine 526 et par son interaction avec des phospholipides. Le domaine SH3 de PIX lie une séquence riche en résidus proline de PAK (p21-activated serine threonine kinase) et le complexe PAK-PIX a été décrit au niveau des points focaux des jonctions adhérentes en contact avec les matrices extracellulaires [4]. Le domaine leucine zipper semble nécessaire à l'initiation du remodelage du cytosquelette et à la formation de replis membranaires [5].…”
Section: Le Complexe Git-pix Une Plate-forme De Régulation Des Gtpaseunclassified
“…Le domaine leucine zipper semble nécessaire à l'initiation du remodelage du cytosquelette et à la formation de replis membranaires [5]. PIX présente une activité GEF pour Rac et Cdc42 in vitro et in vivo et joue un rôle dans la motilité cellulaire et la formation de neurites in vitro [4,6]. Enfin, une mutation dans le gène codant pour αPIX provoque une forme non syndromique de retard mental chez l'homme, une donnée qui souligne la place importante de ce facteur d'échange dans le développement neuronal [7].…”
Section: Le Complexe Git-pix Une Plate-forme De Régulation Des Gtpaseunclassified